Endovascular baroreflex amplification for resistant hypertension: a safety and proof-of-principle clinical study. Issue 10113 (16th December 2017) - Spiering, Wilko; Williams, Bryan; Van der Heyden, Jan; van Kleef, Monique; Lo, Rob; Versmissen, Jorie; Moelker, Adriaan; Kroon, Abraham; Reuter, Hannes; Ansel, Gary; Stone, Gregg W; Bates, Mark; et al.
Summary: Background: Carotid baroreflex activation lowers blood pressure and might have potential application for the treatment of resistant hypertension. We did a proof-of-principle trial with a novel endovascular baroreceptor amplification device, MobiusHD (Vascular Dynamics, Mountain View, CA, USA), in patients with resistant hypertension. Methods: CALM-FIM_EUR was a prospective, first-in-human, open-label study done at six European centres. Eligible patients were adults with resistant hypertension (office systolic blood pressure ≥160 mm Hg despite taking at least three antihypertensive agents, including a diuretic). MobiusHD devices were implanted unilaterally in the internal carotid artery. The primary endpoint was the incidence of serious adverse events at 6 months. Secondary endpoints included changes in office and 24 h ambulatory blood pressure. This trial is registered withClinicalTrials.gov, numberNCT01911897 . Findings: Between December, 2013, and February, 2016, 30 patients were enrolled and underwent successful implantation. Mean age was 52 years (SD 12), 15 patients (50%) were men, and mean antihypertensive use was 4·4 drugs (1·4). Mean office blood pressure was 184/109 mm Hg (18/14) at baseline and was reduced by 24/12 mm Hg (13–34/6–18) at 6 months (p=0·0003 for systolic and p=0·0001 diastolic blood pressure). Mean baseline 24 h ambulatory blood pressure was 166/100 mm Hg (17/14) at baseline and was reduced by 21/12 mm Hg (14–29/7–16) at 6 months (p<0·0001 for systolic and diastolic blood pressure). Five serious adverse events had occurred in four patients (13%) at 6 months: hypotension (n=2), worsening hypertension (n=1), intermittent claudication (n=1) and wound infection (n=1). Interpretation: In patients with resistant hypertension, endovascular baroreceptor amplification with the MobiusHD device substantially lowered blood pressure with an acceptable safety profile. Randomised, double-blind, sham-controlled trials are warranted to investigate the use of this treatment further. Funding: Vascular Dynamics.